The Practice and Prospects of Active Learning Methods in Wollo University - Omer, Mohammed; Dawed, Seid; Talema, Abdurahman (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
This study was mainly designed to assess the practice of active learning in university classrooms. For this purpose instructors from the two campuses of Wollo University were conveniently selected. Data was collected using open and close ended questionnaires, interviews and observation. A total of 70 instructors filled the questionnaire. The type of research employed for this study was descriptive survey research. The collected data were organized, analyzed and interpreted both quantitatively (using percentages and mean values) and qualitatively (using narrations and descriptions). Finally, the results revealed that the instructors did practice active learning but in a low scale. Lecture methods, discussion, cooperative learning, and question-answer methods are mostly used active learning methods. There were various hampering factors affecting the overall practice of active learning strategies including shortage of time, large class size student’s lack of interest for active learning method and shortage of teaching materials. .Based on the findings, reconsidering the modular modality system and revising the training forms for instructors are recommended.